Situation Report: Romania, 15 October 1968 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Romanian-Yugoslav Relations Visit of Apostol to Moscow Ends More Stress on Technical-Economic Aspects of Party Education Literary Prizes for Young Writers Communist Contacts Economic News Miscellaneous